2013
DOI: 10.3103/s1067821213060151
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Ni3Al-Fe alloys by resistivity measurements and differential thermal analysis

Abstract: The Ni 3 Al based intermetallic compound (γ' phase) is the main strengthening phase of foundry heat resistant nickel alloys, which represent an important group of high strength materials used when fabricating the most important details of gas turbine motors [1,2]. Currently the VKNA type alloys based on the Ni 3 Al compound (90% intermetallic phase) are developed and used in industry [3].The Ni 3 Al is ordered according to type L1 2 and occurs in a narrow concentration range near 25 at % Al. Its feature is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…The electrical resistivity ρ of all studied alloys of the Ni-Al-Fe system monotonically increases with increasing temperature, then decreases, and then increases again. A similar behavior of the dependence ρ(t) for Ni 3 Al-based intermetallic alloys was obtained in [13].…”
Section: General-purpose Materialssupporting
confidence: 78%
See 1 more Smart Citation
“…The electrical resistivity ρ of all studied alloys of the Ni-Al-Fe system monotonically increases with increasing temperature, then decreases, and then increases again. A similar behavior of the dependence ρ(t) for Ni 3 Al-based intermetallic alloys was obtained in [13].…”
Section: General-purpose Materialssupporting
confidence: 78%
“…Iron-doped Ni 3 Al ternary alloys have been studied by measuring the electrical resistivity and by differential thermal analysis [13]. It has been shown that the dissolution of Ni 3 Al (γ' phase) is accompanied by a drop in electrical resistivity.…”
Section: General-purpose Materialsmentioning
confidence: 99%
“…Температурный коэффициент удельного сопротивления в режиме охлаждения меньше по абсолютной величине в 4 - 5 раз и отрицателен. Ранее аналогичный результат был получен при измерении удельного электросопротивления жидких жаропрочных сплавов [37]. При охлаждении жидкой стали в этом случае число электронов проводимости z, следовательно, и волновое число Ферми k F увеличивается В соответствие с теорией Фабера-Займана, в данном случае определяющим фактором является рост величины структурного фактора a(2k F ).…”
unclassified